Integrated Dashboard Architecture for Financial Reporting, MIS, and Early Warning Metrics in Liquidity and Market Risk Management - Ahmed, Tanvir (International Journal on Economics, Finance and Sustainable Development, 2024)
The development and strategic significance of an integrated Dashboard Architecture that links Financial Reporting, Management Information Systems (MIS), and early warning metrics related to Liquidity and Market Risk. This framework serves as a comprehensive analytical platform that consolidates financial, operational, and risk data within a real-time interactive environment. The primary objective is to enhance decision-making, improve transparency, and ensure regulatory compliance amidst a rapidly evolving economic landscape. The architecture is designed with a user-centered approach, featuring sophisticated data visualization and advanced analytics that utilize artificial intelligence (AI) and machine learning to transform complex datasets into meaningful insights. By integrating operational, tactical, analytical, and strategic dashboards, the system guarantees that financial reporting aligns with organizational objectives while facilitating the predictive monitoring of liquidity and market risks. The discourse presents real-world applications within financial institutions, highlighting measurable improvements in reporting efficiency, liquidity forecasting, and compliance tracking. Additionally, it evaluates the role of Governance, Risk Management, and Compliance (GRC) frameworks, alongside contemporary Business Intelligence (BI) practices, in enhancing the scalability and sustainability of this architecture. Furthermore, the study identifies emerging trends, such as real-time analytics and AI-enhanced early warning systems, as well as pertinent ethical concerns related to data protection and fairness in automated analysis. Ultimately, the integration of such dashboards signifies a substantial advancement in financial governance, enabling institutions to strengthen their resilience, improve performance, and foster a risk-aware culture that supports informed and proactive decision-making in today's digital financial ecosystem.